An assessment of African Christian beliefs in ancestors in view of a responsible interpretation of 1 Corinthians 8:4-6 within the South African context - Mqala, Lieberman Mxolisi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003